ANALISIS EFEKTIVITAS KOLABORASI ANTARA PEMERINTAH DAN MASYARAKAT DALAM INOVASI PELAYANAN PUBLIK: (Studi Kasus Kelurahan Sukamenanti Baru) - Micko Montana; Ida Farida (Jurnal Progress Administrasi Publik, 2026)
The paradigm of public service delivery has shifted from a top-down approach to a collaborative governance model emphasizing community involvement. This study analyzes the effectiveness of collaboration between government and the community in public service innovation through collaborative creation mechanisms in Sukamenanti Baru Sub-district. A descriptive qualitative approach was employed using in-depth interviews, observation, and documentation. Informants consisted of sub-district officials, neighborhood leaders (RT/RW), and community members who use public services. The analysis of collaboration effectiveness was based on goal achievement, quality of interaction, trust, accountability, and public value creation. The findings indicate that collaboration through the Development Planning Deliberation Forum (Musrenbang) has been effective, particularly in the dimensions of interaction quality and public trust in the sub-district government. Program formulation occurs in a participatory manner and communication runs in two directions. However, collaboration remains constrained by budget limitations and varying levels of community participation. The established collaboration has improved service quality and strengthened public value at the local level. This study contributes to strengthening Musrenbang-based collaboration within the framework of local collaborative governance.   Keywords: Effectiveness; Government Collaboration; Public Service; Village Musrenbang